Gender Roles And The Redefinition Of Family Law: Toward A Modern Family With Justice - Judijanto, Loso; Sistyawan, Dwanda Julisa; Kariyasa, I Made; Amiruddin; Abdulah Pakarti, Muhammad Husni (Mawaddah: Jurnal Hukum Keluarga Islam, 2024)
Gender roles in society have undergone significant changes in recent decades. Social transformation, economic progress, and the increasingly championed gender equality have influenced the dynamics of family law. This research aims to analyze gender roles and the redefinition of family law: towards a modern family with justice. This research uses a qualitative approach with the method of literature study and lawyer analysis. Literature study, collecting data from various written sources, such as books, scientific journals, news articles, and official documents. And discourse analysis, analyzing legal texts, regulations, and mass media. Data analysis uses thematic analysis to identify themes in the data. As well as using interpretative analysis to understand the meaning of the data and produce new findings. The results showed that gender roles are still very strong in Indonesian families, with an unfair division of labor between men and women. This causes women to experience a double burden and injustice in the family. Family law in Indonesia also still contains many elements of discrimination against women, such as in terms of marriage, divorce, and inheritance. Causing women not to get their full rights in the family. To realize a modern family with justice, a redefinition of gender roles and family law is needed. Redefinition of gender roles needs to be done by changing the mindset and behavior of the community about the roles of men and women in the family. Redefinition of family law needs to be done by changing laws and regulations that discriminate against women.